Whose Day in Court is it Anyway? - Gault, Thomas (Victoria University of Wellington Law Review, 2002)
President Gault explores the argument that New Zealand’s appellate system is onerous. While the appeal process is part of the fundamental right to access the courts, the author argues that such values would not necessarily be lost with the adoption of a more streamlined court process. In terms of judicial input, it is noted that judges’ workloads have increased significantly over the past few decades. The author accordingly explores limitations to appeals, including statutory and judicial controls, non-legislative limits, declining of jurisdiction, and the requirement for leave to appeal. President Gault argues for a reduction in the requirements for leave to appeal, having a smaller panel of appellate judges in a judgment, an introduction of extensive requirements to screen out unmeritorious appeals, and confining oral hearings. In terms of judicial output, the author calls for more efficiency in publishing reasons for decisions, such as reducing re-statements of reasons upon appeal.